An analysis of the motivations of volunteers at Humanitarian Firefighters Associations - Almeida, Vasco (2017)
Objectives: To identify the factors that motivate firefighters to volunteer in Portugal and to understand how their characteristics, such as their gender, age, education level, income, and years of volunteering, can influence the types of motivation. Method: A total of 126 volunteer firefighters from two Humanitarian Associations participated, with a mean age of 36.06 years (SD = 12.46), the majority of participants is male (n = 84, 66.7%), is married (n = 53, 42.1%), has secondary education (n = 74, 58.7%), 83 (65.9%) receive a monthly income between €500 and €1000 and has been in the Association for more than 10 years as volunteers (n = 66, 52.4%). The instruments used were a sociodemographic characterization questionnaire and a scale composed of 17 statements elaborated by Ward and Mckillop (2011). Results: The scale has good psychometric characteristics (Cronbach' α = 0.83). In the "Results" we obtain the highest and lowest mean values — "Altruistic - K" indicator (M = 6.27, SD = 1.10) versus "Needs - Q" (M = 4.23, SD = 2.39). In the analysis of motivational variables, according to the sociodemographic characteristics, the indicators with the highest number of statistically significant differences are the "Selfish" of "Human capital" (H), the "Altruistic" (K, L, M) and the "Need" (O) of "Results”. Discussion and Conclusions: The altruism is the dominant factor in explaining the behavior of volunteer firefighters, consistent with previous research on motivation for volunteering. However, when we disaggregate the analysis the results do not always coincide with those found in the literature. The sociocultural context and the specificities of the volunteers' own activity may be responsible for the differences found. Further comparative studies at the international level are necessary, and taking into account the specific characteristics of voluntary firefighter’s activity, namely the issue of risk.